ŞTIINŢA CLUJ, THE REVELATION TEAM OF THE 1953 AND 1954 EDITIONS OF THE WOMEN'S BASKETBALL REPUBLICAN CHAMPIONSHIP - Ildikó MANASSES; Ştefan MAROTI (Cluj University Press, 2015)
The approaching 100ᵗʰ anniversary of the Universitatea Club from Cluj-Napoca gives us reason to look at and reveal the accomplishments of the women's basketball team, Ştiinta Cluj between the years 1949 - 1954. This was a reference period for the history of the basketball section of the Universitatea Club from Cluj. This research draws upon sources such as mass-media articles and other written documents. The first part of the paper focuses on the aspects that have led to the practicing of basketball in the schools and higher education institutions of Cluj and also on the events that made the women's basketball teams from Victor Babes University and Bolyai Janos University participate in local competitions. Then, the paper focuses on the remarkable results of the team and the winning of two national championships titles in 1953 and 1954. Echipa "Știința Cluj", revelația campionatului republican de baschet feminin (1953-1954). Ne-am propus ca, acum când se apropie un secol de existență a Clubului Universitatea din Cluj-Napoca, pe baza unei documentări realizate prin intermediul unor articole de presă și a altor documente, să elaborăm o lucrare, prin intermediul căreia să facem cunoscute realizările echipei feminine de baschet Știința Cluj între anii 1949 - 1954, una din perioadele de referință în istoria secției de baschet din cadrul clubului universitar clujean. În prima parte a lucrării sunt abordate aspecte care au condus la practicarea baschetului în școlile și unitățile de învățământ superior din Cluj și la participarea echipelor feminine de baschet de la Universitatea Victor Babeș și Bolyai János în competițiile locale. În continuare, lucrarea se referă la rezultatele care au făcut posibilă cucerirea celor două titluri de campioane naționale din anii 1953 și 1954.  Cuvinte cheie: istoria sportului, baschet feminin, Știința Cluj